2023
DOI: 10.1080/19490976.2023.2178800
|View full text |Cite
|
Sign up to set email alerts
|

Limosilactobacillus reuteri normalizes blood–brain barrier dysfunction and neurodevelopment deficits associated with prenatal exposure to lipopolysaccharide

Abstract: Maternal immune activation (MIA) derived from late gestational infection such as seen in chorioamnionitis poses a significantly increased risk for neurodevelopmental deficits in the offspring. Manipulating early microbiota through maternal probiotic supplementation has been shown to be an effective means to improve outcomes; however, the mechanisms remain unclear. In this study, we demonstrated that MIA modeled by exposing pregnant dams to lipopolysaccharide (LPS) induced an underdevelopment of the blood vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…The BBB permeability and the expression of tight junction proteins were normalized in germ-free mice colonized with a commensal microbiota [ 68 ]. The probiotic Lactobacillus reuteri improved BBB dysfunction and cognitive deficit in offspring of LPS-induced dams [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The BBB permeability and the expression of tight junction proteins were normalized in germ-free mice colonized with a commensal microbiota [ 68 ]. The probiotic Lactobacillus reuteri improved BBB dysfunction and cognitive deficit in offspring of LPS-induced dams [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these bacteria, L. reuteri stands out due to its ability to produce various bene cial metabolites vital for bodily functions and its profound impact on the microbial community structure 32,33 . Previously studies have shown that L. reuteri can effectively enhance gut and central nervous system development in offspring whose mothers were exposed to high-fat diet, LPS, or antibiotic 34,35 . In our multi-omics analysis, L. reuteri emerged as a key species contributing to ENS development.…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids and metabolic products of bile acids have also been suggested to participate in the communication between the gut microbiota and the brain [ 110 ]. We demonstrated that the modulation of offspring microbiota during lactation through maternal supplementation of probiotics induced taurocholate, taurocholic acid, and taurohyocholic acid crossing the blood–brain barrier [ 43 ]. In this study we have identified that taurine-conjugated choline and tauro-α/β muricholic acid levels were significantly higher in MTERM mice than those in the MNEC mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse fecal samples were submitted to the Microbiome Metagenomics Facility (MMF) of the Duchossois Family Institute (DFI) at the University of Chicago for genomic DNA extraction and subsequent 16S rRNA gene sequencing on the Illumina MiSeq platform, as previously described [ 43 ]. Dada2 (v1.18.0) was used for processing MiSeq 16S rRNA reads with minor modifications in R (v4.0.3) [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%